1964
DOI: 10.1136/hrt.26.2.261
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Blood Pressure Alteration on the Pulse Wave Velocity

Abstract: Determinations of the pulse wave velocity (PWV) in living subjects have shown that higher values are found with increasing age (Rahier, 1961;Simonson and Nakagawa, 1960) and in the presence of hypertension, with or without presumed atherosclerosis, but more so in the former case (Miasnikov, 1960). Woolam et al. (1962) have also shown higher values in diabetics with presumed atherosclerosis, compared with normal subjects.Comparison of PWV values obtained by different workers is difficult because of the variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 7 publications
2
69
0
Order By: Relevance
“…Blood pressure will decrease as a result. In addition, brachial-ankle pulse wave velocity will thus decrease because pulse wave velocity depends on blood pressure at the time of the measurement, as reported by Nye et al [2][3][4]6 Under these conditions, a decrease in CAVI might be due to the relaxation of smooth muscle cells induced by general anesthesia itself and by administration of propofol. The report by Kim described two important features of CAVI: (1) CAVI expression changes over a short period of time, depending on the circulatory condition; and (2) CAVI expression reflects the state of smooth muscle cell contraction.…”
mentioning
confidence: 81%
“…Blood pressure will decrease as a result. In addition, brachial-ankle pulse wave velocity will thus decrease because pulse wave velocity depends on blood pressure at the time of the measurement, as reported by Nye et al [2][3][4]6 Under these conditions, a decrease in CAVI might be due to the relaxation of smooth muscle cells induced by general anesthesia itself and by administration of propofol. The report by Kim described two important features of CAVI: (1) CAVI expression changes over a short period of time, depending on the circulatory condition; and (2) CAVI expression reflects the state of smooth muscle cell contraction.…”
mentioning
confidence: 81%
“…The underlying principle of these devices is based on the relation of the time it takes for a volume of blood (in the form of a pulse) to travel from the heart to a peripheral organ, which could be in the form of pulse transit time (PTT) or pulse arrival time (PAT) [22][23][24]. Algorithms and mathematical models have been proposed and developed to optimize the regression process and calibration of the traveling/delay time ("Time Delay") and BP [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…2, A, B, C, D, the differences in arterial stiffness parameters (Δ) between before and after BPS administration in each hour were calculated Correlations between ΔbaPWV and ΔBlood pressures during 3 hour after Beraprost sodium administration however, it was reported that baPWV includes two components: blood pressure and arterial stiffness 12) . On the other hand, CAVI is independent of blood pressure 11) , so sensitivity in the acute phase for smooth muscle contraction was induced by BPS administration in a small group of middle-aged healthy subjects.…”
Section: Correlation Between Fluctuations Of Blood Pressure and Diffementioning
confidence: 99%
“…Pulse wave velocity (PWV) has been proposed and is used currently [3][4][5] , and many valuable data have been reported [6][7][8][9] ; however, a problem of PWV in clinical use is that PWV itself essentially depends on blood pressure. Hasegawa and coworkers 10) identified PWV variability depending on diastolic pressure from studies using the human aorta, and developed a monograph compensating for PWV by diastolic pressure; however, PWV itself is an indirect method reflecting arterial wall stiffness at the measuring time 11,12) . Recently, the cardio-ankle vascular index (CAVI) was proposed, which essentially represents the stiffness parameter of the aorta, femoral artery and tibial artery.…”
Section: Introductionmentioning
confidence: 99%